Ex Utero Intrapartum Treatment (Exit) Procedure: Indications and Procedural Considerations - Silva, Melissa (Operating Room Nurses Association of Canada Journal, 2020)
Problem identification Ex Utero Intrapartum Treatment (EXIT) has become the optimal delivery strategy in fetuses with airway compromise; however, it remains an extremely rare procedure. This review aims to provide perioperative nurses with an overview of EXIT procedure to enable them to be an effective member of the multidisciplinary team. Literature search An electronic search of the CINAHL, Medline and Scopus databases was undertaken yielding 19 articles for inclusion in this integrative review. The papers included were case studies, case series or retrospectives and describe 42 EXIT procedures with 43 babies. Data evaluation synthesis The most common indication for the EXIT procedure is neck tumours, with other indications being congenital high airway obstruction syndrome (CHAOS), cardiac anomalies, extremely low birth weight (ELBW), micrognathia and congenital diaphragmatic hernia. Literature revealed 41 cases had successful establishment of an airway, with the procedure failing in two cases, both with diagnoses of CHAOS. Implications for perioperative nursing practice or research The role of the perioperative nurse within these cases needs to be explored further. Perioperative nurses need to have the skills and ability to participate as key members of the multidisciplinary team. This can be achieved through in-depth understanding of the topics within this review.